The influence of processing conditions on the mechanical properties of poly(aryl‐ether‐ketone)/polybenzimidazole blends. Issue 33 (11th January 2020) - Jiang, Zhiyuan; Liu, Peng; Chen, Qihui; Sue, Hung‐Jue; Bremner, Tim; DiSano, Lorenzo P.
ABSTRACT: Interest in developing high‐performance blends for niche applications has grown significantly in efforts to meet ever‐increasing harsh environment demands. In this work, four model poly(aryl‐ether‐ketone)/polybenzimidazole (PAEK/PBI) blends were chosen to study the influence of premixing methods, processing, and matrix polymers, on their mechanical properties. Among the model poly(ether ether ketone) (PEEK) and PBI blends, mechanical properties are greatly enhanced by melt premixing. The molding process mainly affects the matrix crystallinity, which in turn greatly influences fracture toughness of the blend. Poly(ether ketone ketone) (PEKK) and PBI blend exhibits a slightly lower tensile strength and fracture toughness than PEEK/PBI due to the differences in inherent properties of PEEK and PEKK matrices and their interfacial interaction with PBI. The processing−structure–property relationship of PAEK/PBI blends is established to help guide optimal design of high‐performance polymer blends for structural applications. © 2020 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48966. Abstract :